Study of the effect of pain on postoperative rehabilitation of patients with uterine malignant tumor - Lv, Xiaohong; Li, Chunlai; Tang, Min; Yuan, Dan; Zhong, Yu; Xie, Yubo (Frontiers in Surgery, 2023)
Objective The relationship between acute postoperative pain (APSP) and health-related quality of life (HRQoL) in patients with uterine malignant tumor after operation was evaluated with self-rating scales, and the influencing factors of postoperative rehabilitation were screened. Methods A total of 102 patients undergoing elective surgery for Gynecology in the First Affiliated Hospital of Guangxi Medical University were included in this study. PCS, SAS, NRS and EQ-5D scales were evaluated 1 day before surgery, and NRS and EQ-5D scales were evaluated 1,3,7,14, and 30 days after surgery. In addition, the general and perioperative information of patients was collected from the medical record system of the hospital. Results From the 1st to the 30th day after operation, the NRS and EQ-5D-5L scores of patients decreased gradually, and EQ-VAS scores increased gradually. NRS score was correlated with EQ-5D score (P < 0.01). Postoperative hospital stay, Education level, PCS score and NRS score (Overall state and Active state) were the principal influencing factors of EQ-5D score (P < 0.05). Patients in the pain group had a later time to get out of bed and eat, a higher incidence of postoperative complications, and a longer postoperative hospital stay (P < 0.05). Endoscopic surgery can reduce postoperative pain and promote postoperative rehabilitation (χ2 = 37.631, P < 0.001). Conclusions The postoperative rehabilitation of patients in the pain group was poor. Minimally invasive surgery can reduce postoperative pain and promote postoperative rehabilitation. EQ-5D score can be used as a subjective index to evaluate postoperative rehabilitation. Trial Registration Chinese Clinical Trial Registry (identifier: ChiCTR2000032759).